2018
DOI: 10.5152/tpd.2018.5884
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii in a Eurasian Badger (Meles meles) Living in Wildlife Areas of Izmir, Turkey

Abstract: Toxoplasma gondii is an obligatory intracellular protozoon parasite that causes toxoplasmosis in humans and all warm-blooded animals. In this study, we aimed to investigate the presence of T. gondii DNA in a Eurasian badger (Meles meles) that was found dead in the wildlife area of Izmir. According to the results of real time polymerase chain reaction, T. gondii REP gene was found to be positive in the Eurasian badger brain homogenate. In conclusion, Eurasian badger, a known carnivore, can be a potential source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…DNA was demonstrated in the brain of a badger (Meles meles); indicating contamination of local waters by T. gondii (Karakavuk et al, 2018a).…”
Section: Parasitologymentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was demonstrated in the brain of a badger (Meles meles); indicating contamination of local waters by T. gondii (Karakavuk et al, 2018a).…”
Section: Parasitologymentioning
confidence: 99%
“…from a zoo in Ankara (Kabak et al ., 2011). Toxoplasma gondii DNA was demonstrated in the brain of a badger ( Meles meles ); indicating contamination of local waters by T. gondii (Karakavuk et al ., 2018 a ).…”
Section: Toxoplasmosis ıN Anımalsmentioning
confidence: 99%
“…In addition, some pathogens, such as Sarcocystis lutrae, Babesia sp. Meles-Hu1, Toxoplasma gondii and Brucella melitensis [21][22][23][24], could infect Asian badgers, thus contributing to decrease in Asian badger populations. In the present study, a large number of mature and young erythrocytes were found in the intestine of hookworms (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies in Portugal and Poland, 50% and 37.5% of the examined animals, respectively, were seropositive [ 302 , 306 ]. The infection in badgers has also been confirmed molecularly in the UK, Poland, Slovakia, and the European part of Turkey [ 303 , 304 , 305 , 306 , 307 ]. Although none of the badgers showed any clinical symptoms related to toxoplasmosis, some authors consider that anorexic and lethargic badgers or those showing an atypical behaviour should be tested for toxoplasmosis [ 300 ].…”
Section: Mustelidaementioning
confidence: 95%